Species-specific, seasonal, inter-annual, and historically-accumulated changes in foliar terpene emission rates in Phillyrea latifolia and Quercus ilex submitted to rain exclusion in the Prades Mountains (Catalonia) (Russian Journal of Plant Physiology, 2011)
Mediterranean vegetation emits large amounts of terpenes. We aimed to study the effects of the decreases in soil water availability forecast for the next decades by global circulation models and ecophysio logical models on the terpene emissions by two widely distributed Mediterranean woody species, Phillyrea latifolia L. and Quercus ilex L. We subjected holm oak forest plots to an experimental soil drought of ca. 20% decrease in soil moisture by partial rainfall exclusion and runoff exclusion. We measured the emission rates throughout the seasons for two years with contrasting precipitation and soil moisture (16.6% average in 2003 vs. 6.4% as average in 2005). Among the detected volatile terpenes, only αpinene and limonene were present in detectable quantities in all of the studied periods. Total terpene emitted ranged from practically zero (spring 2003) to 3.6 and 58.3 μg/(g dry wt h) (winter 2005 and summer 2003 for P. latifolia and Q. ilex, respec tively). A clear seasonality was found in the emission rates (they were the highest in summer in both species) and also in the qualitative composition of the emission mix. Maximum emissions of αpinene occurred in spring and maximum emissions of limonene in winter. Neither the interannual differences in water availabil ity nor the rain exclusion treatment significantly affected the emissions in P. latifolia, but Q. ilex showed by 17% lower emissions during the drier second year of study, 2005, but more than two and threefold increases with the drought treatment in summer 2003 and in summer 2005, respectively, showing historical accumu lated effects. These results, which show increased monoterpene emission under the moderate drought pro duced by the treatment and decreased emission under the severe second year drought, and a much higher sen sitivity to drought in Q. ilex than in P. latifolia, are useful in understanding the behavior of plant volatiles under Mediterranean conditions and in modeling future emission under changing climate conditions. They show that the usage of current models could lead to under and overestimations of the emission under summer dry conditions, because most current algorithms are based on light and temperature only.